Some aspects of the biology of Nassarius kraussianus (Dunker)(Gastropoda : Prosobranchia : Nassariidae), in the Bushman's River estuary, with particular reference to recolonisation after floods - Palmer, Carolyn Gay (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1981)
1. The development of estuarine research in South Africa has been reviewed, and the present state of knowledge assessed. Little is known about many abundant estuarine species, and a previously unstudied prosobranch Nassarius kraussianus (Dunker), was selected for investigation. 2. The study area, a mudflat on the Bushmans River estuary, was divided into three habitat types: supratidal, intertidal and subtidal, each with a particular substratum and pattern of vegetation cover. The distribution of N. kraussianus is associated with the nature of the substratum and the degree of Zostera capensis Setchell cover. 3. A brief review of pertinent literature indicated the necessity of relating population parameters to environmental conditions. 4. The population biology of N. . kraussianus was investigated, and the size frequencies, sex ratios, and male/female size frequencies were recorded over three distinct periods: pre-flood, post-flood and recovery. 5. The Bushmans River flooded in July and August 1979, and the results of the flood have been described. The most immediate result was a period of low salinity, but the most persistant result was the deposition of silt, which had an important effect on the substratum and the Z. capensis beds. 6. The pre-flood population was characterised by patchy distribution, and by a large number of mature adults in relation to juveniles. Females were generally larger than males, and the sex ratio was 1:1. The presence of juveniles in consistantly low numbers indicated that reproduction may have been continuous, but that intraspecific adult/juvenile competition may have kept juvenile numbers low. 7. The post-flood period was characterised by extreme physical conditions, and the survival of a few adults. Juveniles were completely annihilated, and were absent until a few were spawned by the surviving adults towards the end of 1979 . Sex ratio was biased, and females predominated. 8. The recovery period began abruptly with the arrival of a large number of juveniles in the 2, 3 and 4 mm size classes. Recolonisation coincided with habitat recovery, and reqeneration of the Z. capensis cover. Recolonising juveniles grew quickly, reaching adult size in three months. After that, juveniles were spawned on the mudflat by the new population. During this period the sex ratio did not return to the pre-flood 1:1, but remained female biased. Males and females grew at the same rate over the period measured, but females were consistantly larger, indicating that at some stage female growth may be faster. 9. The recolonising juveniles arrived in a regenerated habitat, at a time when temperatures were high, and conditions for growth probably optimal. If intraspecific competition was a feature of the pre-flood population it would have been elimianted in the recovery phase, by the absence of adults. 10. N. kraussianus is apparently omnivorous and proabably not food limited. However, carrion, a limited resource, may be essential for growth to reproductive maturity. Adults and juveniles may compete for this resource, and any juveniles deprived of access to carrion may be stimulated to leave the parental habitat. 11. N. kraussianus is ovoviviparous, and carries up to 5 egg cases within the uterus. Each triangular egg case contains 1 egg which hatches after approximately 3 weeks, as a free swimming veliger. Yeligers metamorphose, and settle after 4-7 days, assuming a benthic mode of life. Ovoviviparity protects the developing embryo from the rigours of environmental extremes, and ensures that embryos are not swept out to sea . Additionally, veligers have a high probability of settling in the parental habitat. 12. This reproductive strategy has been compared with other prosobranchs, and the evolutionary trends within the Prosobranchia, and particularly the Nassariidae, have been related to their dispersal potential. 13. Developmental strategy is intimately related to recolonisation potential. Ovoviviparity, and the lack of pelagic larvae, did not limit the recolonisation potential of N. kraussianus, and recolonisation was probably effected by post-larval juveniles, which may disperse from neighbouring estuaries and coastal pools, by floating in coastal and tidal currents. Post-larval juveniles have two important advantages over larvae. They are less vulnerable to physical extremes, and they have a sturdy crennellated shell which probably affords them protection from predators. 14. Examples of larval recolonisation in estuarine populations have been reviewed, and the most fundamental conclusion of this work is that recolonisation is an important, and probably widespread, adaptation to estuarine conditions in South Africa.
Keywords: Gastropoda -- South Africa -- Eastern Cape; Estuarine biology -- South Africa -- Eastern Cape; Prosobranchia -- South Africa -- Eastern Cape